Patient Safety in Tehran University of Medical Sciences General Hospitals, Iran - Mohammad Arab; Ali Akbari Sari; Elham Movahed Kor; Mostafa Hosseini; Shiva Toloui Rakhshan; Mohammad Ezati (Tehran University of Medical Sciences, 2013)
Background: It is important to focus on creating opportunities for patients' participation at all levels of health systems in order to promote their ability to improve patient safety and quality of services. The general aim of this study was to determine patient safety level in Tehran University of Medical Sciences' (TUMS) general hospitals, Tehran, Iran from patients' perspective and to determine the contributory factors on their perspective.Methods: This was a cross-sectional study. In the spring 2011, the list of clinical departments of the six general hospitals affiliated to TUMS was obtained through the Website of TUMS. By using stratified random sampling, the sample size was calculated 300 patients. Data were collected by using a structured questionnaire and its validity and reliability were acceptable. Descriptive statistics, linear regression and logistic regression were used for analyzing the data.Results: Totally, 60% of patients were female. Patient safety was evaluated high by 60% of respondents. The unmarried or educated or employed individuals tend to score lower than others.Conclusion: TUMS's general hospitals are enough safe from patients' perspective, patient safety should be improved. In clinical governance, contributing patients' perspective to the improvement of patient safety reforms is critical in generating new models of good practice.